Micro Franchising: - Zindiye, Stanislous; Shumba, Knowledge; Maluleke, Tiyisani Shiella (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study aims to investigate how microfranchising can be used as a tool for increasing self-employment and to fight poverty in Thohoyandou. Design/methodology/approach: A qualitative research approach was employed with a sample of eight participants that comprised microfranchise businesses in Thohoyandou. The convenience sampling technique was adopted to select the participants. Primary data was gathered through in-depth interviews using a structured interview guide. Findings: The study's findings established that microfranchising tools such as business in a box, comprehensive training, employment creation, good marketing mix, improved asset base, improved standard of living, increased economic growth and market gap help reduce social ills. Practical implications: The research managed to unravel the strategies that can be adopted to enhance microfranchising in increasing self-employment and alleviating poverty. Originality/value: There are limited studies on microfranchising in South Africa. Paper type: Research Paper